2020
DOI: 10.1002/bies.201900202
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Schizophrenia

Abstract: Schizophrenia (SCZ) is a severe neurodevelopmental disorder affecting 1% of populations worldwide with a grave disability and socioeconomic burden. Current antipsychotic medications are effective treatments for positive symptoms, but poorly address negative symptoms and cognitive symptoms, warranting the development of better treatment options. Further understanding of SCZ pathogenesis is critical in these endeavors. Accumulating evidence has pointed to the role of mitochondria and metabolic dysregulation in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 147 publications
2
21
0
Order By: Relevance
“…A number of genes involved in mitochondrial function and responsive to PGC-1α overexpression in human neuroblastoma cells [70] are reduced, including ATP5A1 [259,260], glutamic-oxaloacetic transaminase 1 (GOT1; [259]), IDH3A [260], and malate dehydrogenase 1 (MDH1; [260]). These findings are concordant with reports of mitochondrial dysfunction in autism (reviewed in [263] and [264]) and schizophrenia (reviewed in [265]). Transcriptional studies also reported decreased expression of PVALB [259,260], SYT2, NEFH, and glutamic acid decarboxylase 1 and 2 (GAD1 and GAD2) [259], indicating either the loss of expression of these markers and mitochondrial genes in existing interneuron populations or the loss of these neurons.…”
Section: Developmental Disorderssupporting
confidence: 91%
“…A number of genes involved in mitochondrial function and responsive to PGC-1α overexpression in human neuroblastoma cells [70] are reduced, including ATP5A1 [259,260], glutamic-oxaloacetic transaminase 1 (GOT1; [259]), IDH3A [260], and malate dehydrogenase 1 (MDH1; [260]). These findings are concordant with reports of mitochondrial dysfunction in autism (reviewed in [263] and [264]) and schizophrenia (reviewed in [265]). Transcriptional studies also reported decreased expression of PVALB [259,260], SYT2, NEFH, and glutamic acid decarboxylase 1 and 2 (GAD1 and GAD2) [259], indicating either the loss of expression of these markers and mitochondrial genes in existing interneuron populations or the loss of these neurons.…”
Section: Developmental Disorderssupporting
confidence: 91%
“…Ample evidence has been accumulated, indicating a multifaceted mitochondrial dysfunction in schizophrenia (reviewed in [ 198 , 200 , 201 ]). Primarily, morphological and functional abnormalities of mitochondria in schizophrenia were detected.…”
Section: Molecular Mechanisms Of Oxidative Stress In the Pathogenementioning
confidence: 99%
“…These changes may be associated with impaired gene expression. Indeed, the decreased expression of numerous mitochondria-related genes (encoding, for example, NADH-ubiquinone oxidoreductase core subunits V1, V2, and S1 and cytochrome c oxidase) was observed in postmortem brain tissues of patients with schizophrenia in smaller-scale studies [ 201 ]. As stated above, transcriptomic and proteomic studies in large samples also confirmed the impaired expression of mitochondrial genes in brain tissues [ 98 , 103 , 207 ].…”
Section: Molecular Mechanisms Of Oxidative Stress In the Pathogenementioning
confidence: 99%
See 2 more Smart Citations